2007
DOI: 10.1093/imamat/hxl033
|View full text |Cite
|
Sign up to set email alerts
|

Effective wave propagation in a prestressed nonlinear elastic composite bar

Abstract: The problem of determining the effective incremental response of nonlinearly elastic composite materials given some initial pre-stress, is of interest in numerous application areas. In particular the case when small amplitude elastic waves pass through a pre-stressed inhomogeneous structure is of great importance. Of specific interest is how the initial finite deformation affects the microstructure and thus the subsequent response of the structure. Modelling this effect is in general extremely difficult.In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 41 publications
0
61
0
Order By: Relevance
“…Therefore, predeformation allows for the controllable variation of elastic moduli and dispersion properties [221,[223][224][225]. Such tunability can be further enhanced by triggering mechanical instabilities along the loading path, since these result in dramatic geometric reconfigurations.…”
Section: Tunable Acoustic Metamaterialsmentioning
confidence: 99%
“…Therefore, predeformation allows for the controllable variation of elastic moduli and dispersion properties [221,[223][224][225]. Such tunability can be further enhanced by triggering mechanical instabilities along the loading path, since these result in dramatic geometric reconfigurations.…”
Section: Tunable Acoustic Metamaterialsmentioning
confidence: 99%
“…Nonlinear pre-stress can be extremely useful in practice, allowing us to tune materials in order to permit or restrict waves of specific frequency ranges to propagate through the structure. This property was described by Parnell [20] and discussed further in subsequent articles in different contexts [7], [1].…”
Section: Introductionmentioning
confidence: 71%
“…When the medium in question is inhomogeneous (for example a fibre-reinforced, or particulate composite material), where the host phase is nonlinear-elastic, pre-stress will almost always lead to non-homogeneous stretch distributions, except in very special cases (see e.g. [20]). Degtyar et al [5] analysed the case of stressed composites where residual stresses occur in the vicinity of inhomogeneities, in the context of linear elasticity and a self consistent scattering formulation of the effective wavenumber was used.…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed above, bistable or multistable building blocks in periodic solids and structures also promise interesting nonlinear dynamic effects, including solitary-wave propagation, which provides opportunities to focus acoustic signals in mechanical metamaterials [4,80,81]. Homogeneous solids undergoing finite elastic deformation [82] as well as periodic media experiencing nonlinear elastic instabilities [83] have been shown to exhibit acoustic band gaps that are controllable by the amount of nonlinear predeformation, yet the investigated waves again operate in the linear elastic regime. To date, only one example of a periodic elastic mechanical system has been reported that produces SineGordon solitons by allowing a kink propagation in the form of elastically connected rotating pendulums [84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%